Pembelajaran Geografi Berbasis Teknologi Digital: Studi Persepsi Siswa dan Relevansinya dengan Sustainable Development Goals 4 - Musyawarah, Rahma; Hasriyanti, Hasriyanti; Kalsum, Ummu (PT. Pubsains Nur Cendekia, 2025)
The SDGs 4 agenda emphasizes equitable education through digital technology, which, although helpful in visualizing the geosphere concept in Geography learning, is still hampered by infrastructure and digital literacy in non-urban schools. This study aims to analyze students' perceptions of digital technology-based Geography learning at Senior High School 18 Bone. The research instrument was a dichotomous questionnaire, while the data were analyzed using descriptive statistics. The results showed that 74% of students were interested in digital technology-based learning, 81.2% considered the learning useful, 77.2% felt the technology was easy to use, and 72.4% responded positively to the availability of supporting facilities. These results confirm that the application of digital technology contributes to the achievement of SDGs 4, particularly in targets 4.1 (improving the quality of learning), 4.4 (strengthening digital literacy), 4.7 (environmental awareness and spatial thinking), and 4.a (availability of inclusive learning facilities). Thus, digital technology-based Geography learning in non-urban schools is considered effective and relevant in supporting sustainable education.